Epilogues and last words in Shakespeare: Exploring patterns in a small corpus. (22nd August 2020) - Findlay, Alison
This article considers the linguistic features of the speeches that end Shakespeare's plays, some of which are formally labelled as Epilogues. It introduces a play's last words as a type of paratext using the theoretical models devised by Genette (1997), and then considers the material evidence surrounding Epilogues, a specific form of last words, using research on their ephemeral and occasional nature by Stern (2009). The difficulties of using corpus methods in the case of small, specialist subcorpora of paratexts is then considered, and the methodology adopted to extract and present the results is outlined. The demonstrates features of the Last Words corpus: how pronouns raise questions about the speaker's stance (with reference to work by Goffman (1979) and Messerli (2017)); how these speeches deploy the language of inclusivity; how they interpellate spectators or readers to promote a specific agenda. Because last words enact the fragile liminal moment where characters, actors and audience are united by their experience of the performance, the article considers their retrospective and prospective orientation. It demonstrates how the prominence of verbs like 'shall' and 'will' can be used for marketing purposes. The problems raised by uneven dispersion of terms are discussed leading to a case study of the Epilogue of As You Like It which demonstrates how its use of language is deliberately linked to the discursive world of the play which precedes it.